BIOECOLOGICAL ASPECTS OF COMMON HOP (HUMULUS LUPULUS L) IN THE FIRST YEAR OF VEGETATION IN THE CONDITIONS OF KARAKALPAKSTAN - Sarsenbaev Amaniyaz Aminbaevich (World Scientific Research Journal, 2025)
This article explores the bioecological characteristics of common hop (Humulus lupulus L.) during its first year of vegetation under the specific soil and climatic conditions of Karakalpakstan. The study focuses on plant growth dynamics, morphological development, and adaptive responses to arid environmental factors such as high salinity, low precipitation, and temperature fluctuations typical of the region. Experimental observations revealed that during the initial vegetation period, the root system of the common hop develops intensively, ensuring anchorage and water absorption even under moderate drought stress.Leaf morphology and chlorophyll content were measured and showed high photosynthetic activity during early summer, with a gradual decline by late August due to heat stress. The research also highlights phenological phases, including germination, stem elongation, and cone formation, and provides insights into the optimal sowing time and irrigation schedules for successful cultivation in Karakalpakstan. These findings are vital for the regional development of medicinal and industrial crops and demonstrate that Humulus lupulus L. has significant potential for ecological adaptation and economic utilization in semi-desert landscapes.